The systems of purification of the melting furnaces discharge - L. E. Rovin; S. L. Rovin (Литьë и металлургия, 2002)
In the experience there is examined the problem of clarification of discharge from melting furnaces, there is being analyzed the existing situation on the most of Belarusian enterprises and are offered the ways of solution of this problem, including the measures on optimization of melting process and modernization of operating furnaces and also the creation of purification systems.